Barriers of Distance Learning in studied English for Logistics: Literature Review - Saskia Kanisaa P; Dwi Novi Wulansari (Journal of Logistics and Supply Chain, 2021)
In 2020, we have to face another big problem not only in Indonesia but the whole world suffers from a global pandemic, named the Covid-19 virus. Education has also received a significant impact that made the government and universities keep on track on how to keep education in Indonesia running well, but without endangering the health of all interested parties. Thanks to technology, we can use the distance learning method for studies for now. Unfortunately, in Indonesia, there are many barriers to use this method. In this paper, the authors use a literature review method for knowing the barriers of distance learning in Technical and Vocational Education Training (TVET) especially for study English for Logistics Engineer.